Erythrocyte Adhesion of Merozoite Surface Antigen 2c1 Expressed During Extracellular Stages of Babesia orientalis - Nie, Zheng; Ao, Yangsiqi; Wang, Sen; Shu, Xiang; Li, Muxiao; Zhan, Xueyan; Yu, Long; An, Xiaomeng; Sun, Yali; Guo, Jiaying; Zhao, Yangnan; He, Lan; et al. (Frontiers in Immunology, 2021)
Babesia orientalis, a major infectious agent of water buffalo hemolytic babesiosis, is transmitted by Rhipicephalus haemaphysaloides. However, no effective vaccine is available. Essential antigens that are involved in parasite invasion of host red blood cells (RBCs) are potential vaccine candidates. Therefore, the identification and the conduction of functional studies of essential antigens is highly desirable.. Here, we evaluated the function of B. orientalis merozoite surface antigen 2c1 (BoMSA-2c1), which belongs to the variable merozoite surface antigen (VMSA) family in B. orientalis. We developed a polyclonal antiserum against the purified recombinant (r)BoMSA-2c1 protein. Immunofluorescence staining results showed that BoMSA-2c1 was expressed only on extracellular merozoites, whereas the antigen was undetectable in intracellular parasites. RBC binding assays suggested that BoMSA-2c1 specifically bound to buffalo erythrocytes. Cytoadherence assays using a eukaryotic expression system in vitro further verified the binding and inhibitory ability of BoMSA-2c1. We found that BoMSA-2c1 with a GPI domain was expressed on the surface of HEK293T cells that bound to water buffalo RBCs, and that the anti-rBoMSA2c1 antibody inhibited this binding. These results indicated that BoMSA-2c1 was involved in mediating initial binding to host erythrocytes of B. orientalis. Identification of the occurrence of binding early in the invasion process may facilitate understanding of the growth characteristics, and may help in formulating strategies for the prevention and control of this parasite.